Therapeutic immunomodulation by rationally designed nucleic acids and nucleic acid nanoparticles - Panigaj, Martin; Skelly, Elizabeth; Beasock, Damian; Marriott, Ian; Johnson, M. Brittany; Salotti, Jacqueline; Afonin, Kirill A. (Frontiers in Immunology, 2023)
The immune system has evolved to defend organisms against exogenous threats such as viruses, bacteria, fungi, and parasites by distinguishing between “self” and “non-self”. In addition, it guards us against other diseases, such as cancer, by detecting and responding to transformed and senescent cells. However, for survival and propagation, the altered cells and invading pathogens often employ a wide range of mechanisms to avoid, inhibit, or manipulate immunorecognition. As such, the development of new modes of therapeutic intervention to augment protective and prevent harmful immune responses is desirable. Nucleic acids are biopolymers essential for all forms of life and, therefore, delineating the complex defensive mechanisms developed against non-self nucleic acids can offer an exciting avenue for future biomedicine. Nucleic acid technologies have already established numerous approaches in therapy and biotechnology; recently, rationally designed nucleic acids nanoparticles (NANPs) with regulated physiochemical properties and biological activities have expanded our repertoire of therapeutic options. When compared to conventional therapeutic nucleic acids (TNAs), NANP technologies can be rendered more beneficial for synchronized delivery of multiple TNAs with defined stabilities, immunological profiles, and therapeutic functions. This review highlights several recent advances and possible future directions of TNA and NANP technologies that are under development for controlled immunomodulation.